The Development of Multicultural Education Implementation Model in Social Science Learning using Contextual Teaching and Learning (CTL) - Musadad, Akhmad Arif; I, C. Dyah Sulistyaningrum; S, Leo Agung (VNU Journal of Science: Education Research, 2018)
This research aimed to describe the development of multicultural education implementation model in Social Science learning using Contextual Teaching Learning (CTL) in Junior High Schools of Surakarta City, including: (1) description of model validation result by expert team, (2) description of model field trial result, and (3) description of final model form. This research was conducted using research and development design. The subject of research consisted of students and Social Science teachers in Junior High Schools of Surakarta City. This research was conducted in three stages: (1) preliminary study, (2) model development, and (3) model evaluation. Preliminary study was conducted in the first year, and the result was used as the basis for conducting the next stage in the second year. In the second year, model was developed in the following procedure: (1) development and readability test, (2) model validation test by expert team, (3) model trial in the field, and (4) model perfection. The results of research were as follows. (1) Expert team’s evaluation on multicultural education implementation draft model and set in Social Science learning using CTL involve six aspects: a) learning model structure, b) learning model advantage, c) learning model effectiveness, d) learning model visibility, e) learning set, and f) learning guidance. The expert team’s mean score on learning draft model and set is 3.48. It means that expert team considered that multicultural education implementation model in Social Science using CTL is good. (2) Individual trial obtained mean score of 3.45. The mean score of group trial increased to 3.53 and the score of small-scale trial increased to 3.58. So, overall the participants of trial considered that the model developed was very good. (3) The final form of multicultural education implementation model in Social Science learning using CTL included: rationale, definition, syntax of model, and objective and learning implementation plan.